The Pharisees - Sievers, Joseph 1948-; Levine, Amy-Jill 1956- (Chicago Wm. B. Eerdmans Publishing Co., 2021)
Intro -- Title Page -- Copyright -- Contents -- List of Illustrations and Tables -- Preface -- Acknowledgments -- List of Abbreviations -- Prelude: What's in a Name? -- 1. Interpreting the Name "Pharisee"-Craig E. Morrison -- Part 1: Historical Reconstruction -- 2. In Search of the Origins of the Pharisees-Vasile Babota -- 3. Purity Concerns and Common Judaism in Light of Archaeology-Eric M. Meyers -- 4. Pharisaic Halakah as Emerging from 4QMMT-Vered Noam -- 5. Josephus's Pharisees-Steve Mason -- 6. Paul, the Perfectly Righteous Pharisee-Paula Fredriksen -- 7. Pharisees and Sadducees Together in Matthew-Henry Pattarumadathil -- 8. Polemic against the Pharisees in Matthew 23-Adela Yarbro Collins -- 9. Luke-Acts as a Source for the History of the Pharisees-Hermut Löhr -- 10. Pharisees in the Fourth Gospel and One Special Pharisee-Harold W. Attridge -- 11. The Shared Image of Pharisaic Law in the Gospels and Rabbinic Tradition-Yair Furstenberg -- 12. How Close Were Jesus and the Pharisees?-Jens Schröter -- 13. The Pharisees and the Rabbis-Günter Stemberger -- Part 2: Reception History -- 14. "Pharisees" and Early Christian Heresiology-Matthias Skeb -- 15. A Statistical Approach to Pharisaios and Pharisaikos in the Greek Fathers-Luca Angelelli -- 16. The Forgotten Pharisees-Shaye J. D. Cohen -- 17. The Perushim in the Understanding of the Medieval Jewish Sages-Abraham Skorka -- 18. The Pharisees in the Theology of Martin Luther and John Calvin-Randall Zachman -- 19. The Pharisees in Art-Angela La Delfa -- 20. A Brief, Personal History of the Oberammergau Passion Play-Christian Stückl -- 21. The Pharisees on Film-Adele Reinhartz -- 22. The Pharisees in Modern Scholarship-Susannah Heschel and Deborah Forger -- 23. A Textbook Case-the Pharisees in Catholic Religion Textbooks-Philip A. Cunningham -- Part 3: Looking to the Future.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung